Surface fluxes and boundary layer recovery in TOGA COARE: sensitivity to convective organization - Saxen, Thomas R., author (Colorado State University. Libraries, 1996)
Shipboard radar data collected during the Tropical Ocean Global Atmospheres Coupled Ocean-Atmosphere Response Experiment (TOGA COARE) were used in conjunction with surface meteorological data from the Woods Hole Oceanographic Institute's Improved Meteorology (IMET) buoy to describe in detail how four different classifications of convective systems affect the atmospheric boundary layer and alter the surface fluxes of heat, moisture, and momentum. Atmospheric convective systems observed by radar were separated into four classifications based on spatial scale (subMCS vs. MCS scale) and horizontal morphology (non-linear vs. linear organization). Composite analyses of the surface fluxes along with the pertinent bulk variables have been constructed for each of the four classes of convective organization. During the compositing process, the convectively active and recovery periods were separated, allowing both of these distinctly different phases to be accurately represented in the final composite analyses. All four types of convective organization affected the boundary layer and altered the surface fluxes in a similar manner. However, the duration and magnitude of the response was highly dependent on the type of convective organization. The sub-MCS scale events tended to develop in environmental conditions which inhibited their upscale growth and accordingly produced the weakest and shortest response at the surface. The MCS scale events, on the other hand, tended to develop in environmental conditions which allowed the systems to intensify and organize, including strong convective scale downdrafts, which promoted a greater response at the surface. The MCS scale events also had a significant amount of stratiform precipitation associated with them which slowed the rate at which the boundary layer recovered to the pre-convective state. This, combined with the fact that the MCS scale events perturbed the boundary layer to a greater extent, accounted for the recovery phase of the MCS scale events being more than twice as long as the sub-MCS scale events.
December 1996.
Also issued as author's thesis (M.S.) -- Colorado State University, 1997.
Keywords: Ocean-atmosphere interaction; Boundary layer (Meteorology); Convection (Meteorology)